Media and communication in Nigeria
1 online resource.
Keywords: "Communications are changing rapidly around the world, but particularly in Africa, where citizens are embracing digital technologies not only to improve interpersonal communication but also the state of their financial well-being. This book investigates these transformations in Nigeria's booming communication industry. The book traces communications in Nigeria back to pre-colonial indigenous communications, through the development of telecommunications, broadcasting networks, the press, the Nigerian film industry ('Nollywood'), and on to the digital era. At a time when Western voices still dominate the academic literature on communication in Africa, this book is noteworthy in drawing almost exclusively on the expertise of Nigerian-based authors, critique the discipline from their own lens, and providing an important contribution to the decolonization of communication studies. The authors provide a holistic analysis of the sector, encompassing print journalism, broadcast journalism, public relations, advertising, film, development communication, organizational communication, and strategic communications. Analysis of the role of digital technologies is woven throughout the book, concluding with a final section theorising the future of communication studies in Nigeria in the light of the digital media revolution. Robust in its theoretical and methodological underpinnings, this book will be an important reference for researchers of Media and Communication Studies, and those working on Africa specifically"--